Isolation, Genotyping, and Mouse Virulence Characterization of Toxoplasma gondii From Free Ranging Iberian Pigs - Fernández-Escobar, Mercedes; Calero-Bernal, Rafael; Regidor-Cerrillo, Javier; Vallejo, Raquel; Benavides, Julio; Collantes-Fernández, Esther; Ortega-Mora, Luis Miguel (Frontiers in Veterinary Science, 2020)
The present study aimed to isolate and perform molecular and phenotypic characterization of Toxoplasma gondii strains infecting Iberian pigs bred under semi-free conditions and destined for human consumption. Blood and heart tissue samples from 361 fattening pigs from 10 various herds selected in the main areas of Iberian pig production were collected at a slaughterhouse; the sera were tested for anti-T. gondii antibodies using a commercial indirect ELISA kit, and a mouse bioassay was carried out using heart muscle of seropositive individual representatives from each geographical location. Seventy-nine (21.9%) of the 361 animals tested positive for anti-T. gondii antibodies according to the serology test. Fifteen samples of myocardial tissue were subjected to bioassay and 5 isolates (TgPigSp1 to TgPigSp5) were obtained. The isolates were characterized by using 11 PCR-RFLP genetic markers; three isolates had a ToxoDB #3 genotype (3/5) and two isolated had a ToxoDB #2 genotype (2/5). The TgPigSp1 and TgPigSp4 isolates were selected for virulence in mice characterization as instances of each different RFLP-genotype found. The TgPigSp1 isolate (#2 genotype) was virulent in mice with notable cumulative mortality (87.5%) and morbidity rates (100%); the TgPigSp4 (#3) was nonvirulent and triggered mild clinical signs in 42.1% of inoculated mice. Infection dynamics and organ distribution of both isolates were analyzed; the data revealed significant differences, including substantially higher parasite load in the lung during the acute phase of infection, in mice infected with TgPigSp1 than in the case of TgPigSp4 (median parasite load 7.6 vs 0 zoites/mg, respectively; p<0.05). Furthermore, degrees of severity of detected histopathological lesions appeared to be related to higher parasite burdens. Taking into account the unexpectedly high mortality rate and parasite load associated with the clonal genotype III, which is traditionally considered nonvirulent in mice, the need for further investigation and characterization of the T. gondii strains circulating in any host in Europe is emphasized.